Existence Results for some p(x)-Kirchhoff Type Problem with Dependence on the Gradient - Yacini, Soukaina; Allalou, Chakir; Hilal, Khalid (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present paper, we investigate the existence of at least one weak solution to the Dirichlet boundary value problem involving the p(x)-Kirchhoff type equation with a reaction term depending also on the gradient (convection). Our result is obtained by means of the theory of topological degree and the theory of variable exponent Sobolev spaces.